2013
DOI: 10.2174/1567205011310060002
|View full text |Cite
|
Sign up to set email alerts
|

The Role of -Synuclein in Neurodegenerative Diseases: >From Molecular Pathways in Disease to Therapeutic Approaches

Abstract: Parkinson disease (PD) is the second most prevalent neurodegenerative disorder after Alzheimer's disease (AD). The formation of the cytoplasmic inclusions named "Lewy bodies" in the brain, considered to be a marker for neuronal degeneration in PD and dementia with Lewy bodies. However, Lewy bodies (LBs) are also observed in approximately 60 percent of both sporadic and familial cases with AD. LBs consist of fibrils mainly formed by post-translational modified α-synuclein (α-syn) protein. The modifications can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Similarly, the enrichment of metabolic pathways, organismal systems including nervous and immune system pathways, and common signaling pathways of the environmental information processing category is also expected and well-supported in the literature [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Interestingly, several genetic information processing pathways, including cell cycle regulation and DNA replication and repair, were found to be enriched.…”
Section: Snp-enriched Pathways and Associated Crosstalkssupporting
confidence: 56%
“…Similarly, the enrichment of metabolic pathways, organismal systems including nervous and immune system pathways, and common signaling pathways of the environmental information processing category is also expected and well-supported in the literature [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Interestingly, several genetic information processing pathways, including cell cycle regulation and DNA replication and repair, were found to be enriched.…”
Section: Snp-enriched Pathways and Associated Crosstalkssupporting
confidence: 56%
“…α‐syn is a neuroprotein widely expressed in the brain and is involved in various neurodegenerative diseases (Al‐Mansoori, Hasan, Al‐Hayani, & El‐Agnaf, ; Melki, ). Studies have reported that various structural forms of pathological state α‐syn, such as fibrils, fibers, oligomers, and amorphous oligomers, and their posttranslational modifications, such as phosphorylation, nitration, and ubiquitination, are neurotoxic (Chen & Feany, ; Cremades et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous pathways and targets are being explored for Parkinson’s disease and Alzheimer’s disease, and strategies targeting the misfolding of proteins such as tau, amyloid, and α-synuclein are also likely to be relevant for dementia with Lewy bodies and Parkinson’s disease dementia. Modulating α-synuclein toxicity, for example by targeting heat shock proteins 156,157 or by manipulating chaperone-mediated autophagy, 158 are promising strategies. Alternative strategies include potential neuroprotective drugs such as adenosine-receptor blockers, monoamine oxidase inhibitors, antioxidative drugs, nerve growth factor, and stem-cell therapy, and multi-target drugs with neuroprotective and neurorestorative activity.…”
Section: Future Researchmentioning
confidence: 99%